1999
DOI: 10.1007/s001980050143
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Osteoporosis by Educational Level in a Cohort of Postmenopausal Women

Abstract: To evaluate whether the prevalence of osteoporosis and related risk factors might be influenced by the level of education, as has been demonstrated for many other chronic diseases, 6160 postmenopausal women at their first densitometric referral were interviewed about reproductive variables, past and current use of estrogens, prevalence of chronic diseases, and lifestyle factors such as calcium intake, physical activity, smoking and overweight. This sample was stratified by years of formal education. Densitomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
80
3
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(96 citation statements)
references
References 27 publications
11
80
3
2
Order By: Relevance
“…Late menarche is associated with low bone mass at several sites of the skeleton in both premenopausal (1)(2)(3) and postmenopausal women. (4)(5)(6)(7) These findings are supported by observations that late pubertal maturation is linked to an increased risk of vertebral and nonvertebral fragility fractures. (8)(9)(10)(11) Retrospective epidemiological studies have shown that the inverse relationship between bone mineral mass or density and age of menarche seen in premenopausal women has generally been ascribed to the duration of sex hormone exposure up to the time of peak bone mass.…”
supporting
confidence: 56%
“…Late menarche is associated with low bone mass at several sites of the skeleton in both premenopausal (1)(2)(3) and postmenopausal women. (4)(5)(6)(7) These findings are supported by observations that late pubertal maturation is linked to an increased risk of vertebral and nonvertebral fragility fractures. (8)(9)(10)(11) Retrospective epidemiological studies have shown that the inverse relationship between bone mineral mass or density and age of menarche seen in premenopausal women has generally been ascribed to the duration of sex hormone exposure up to the time of peak bone mass.…”
supporting
confidence: 56%
“…Education above college level was shown to be preventive against osteoporosis/osteopenia among the premenopausal women involved in the current study. This was consistent with some previous studies where higher educational level had a protective role on osteoporosis [25,26,27,28]. Education plays a good role in bringing awareness to individuals about most diseases and their risk factors.…”
Section: Discussionsupporting
confidence: 92%
“…Socioeconomic status has been identified as a factor in hip fractures. [13][14][15] Hip fractures are also reported to be more common in urban areas 16,17 and more northern latitudes. 18 Diabetes is a significant risk factor for fractures, 19,20 and any putative benefit of type 2 diabetes in terms of enhanced bone mass appear to be overwhelmed by other adverse consequences of this disorder.…”
Section: Discussionmentioning
confidence: 99%